Social Influence, Price, and Product Traits on E-Cigarette Use: Perceived Benefits as Mediator, Social Media and Regulation as Moderators (Surabaya Adult Smokers) - Paramitha, Intan Tirzana; Cempena, Ida Bagus; Budiarti, Endah (PT Inovasi Pratama Internasional, 2025)
This study aimed to examine the impact of social influence, price perception, and product characteristics on the decision to use e-cigarettes, with perceived benefits as a mediator and social media and government regulations as moderators. The research adopted a quantitative approach with a causal-explanatory design, targeting legally adult smokers in Surabaya who use or have switched to e-cigarettes and are active on social media. Using purposive sampling, 182 respondents were selected, and data were analyzed using SEM-PLS 4.0. The findings revealed several key insights: (1) Social factors, price perception, and product characteristics all positively and significantly influenced e-cigarette usage decisions. (2) These three factors also significantly enhanced perceived benefits, which in turn positively affected usage decisions. However, (3) social media and government regulations did not significantly moderate the relationship between perceived benefits and e-cigarette use, suggesting that individual consumer context plays a stronger role than external influences. The study’s implications highlight that manufacturers should prioritize product quality and competitive pricing to attract consumers, while policymakers should focus on public education regarding e-cigarette safety and risks. Since social media and regulations showed limited moderating effects, tailored strategies based on consumer behavior may be more effective than broad regulatory measures. This research contributes to understanding the drivers of e-cigarette adoption, offering practical insights for businesses and regulators in Indonesia’s growing vaping market